Characterization of pectin from grapefruit peel: A comparison of ultrasound-assisted and conventional heating extractions. (December 2016) - Wang, Wenjun; Ma, Xiaobin; Jiang, Peng; Hu, Lyulin; Zhi, Zijian; Chen, Jianle; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: In the present study, properties of pectin from grapefruit ( Citrus paradisi Macf. cv. Changshanhuyou) peel extracted by ultrasound-assisted extraction (UP), were compared with those of pectin extracted by conventional heating extraction (CP). UP exhibited a lower molecular weight ( M w ) but more concentrated M w distribution than CP. Although both UP and CP were high-methoxyl pectin, UP showed significantly lower degree of methoxylation but higher degree of acetylation. Monosaccharide composition analysis showed that the molecular structure of UP possessed more branch chains than CP, but little difference was observed in the chemical structures between UP and CP from FT-IR and NMR spectra analysis. X-ray diffraction (XRD) analysis further confirmed that UP had decreased level of crystallinity than CP. Moreover, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated UP had higher thermal stability. UP exhibited lower apparent viscosity and elasticity than CP, showing that ultrasound affected the rheological properties of pectin. Besides, antioxidant activity and lipase inhibitory capacity of UP significantly enhanced compared with CP. Graphical abstract: Highlights: Structure and properties of pectin were affected by different extraction methods. Ultrasonic extracted pectin had lower molecular weight and polydispersity. Ultrasonic extracted pectin had higher percentage of side chains. Thermal stability of ultrasonic extracted pectin were advantageous. Ultrasonic extracted pectin exhibited excellent bioactivity.